Complete mitochondrial genome of the peninsula cooter (Pseudemys peninsularis, Testudines: Emydidae) in Korea - Dayeon Chung; Jaehong Park; Seungju Cheon; Seung-Min Park; Ha-Cheol Sung; Dong-Hyun Lee (Mitochondrial DNA. Part B. Resources, 2022)
The complete mitochondrial genome of Pseudemys peninsularis in Korea was sequenced and characterized. The mitochondrial genome is constituted of 37 genes (13 protein-coding genes, 22 transfer RNA genes, and two ribosomal RNA genes) and a noncoding region. Phylogenetic analysis based on the 13 protein-coding gene sequences showed that P. peninsularis has closer relationship with Chrysemys picta than Trachemys scripta elegans. This is the first case for a complete mitochondrial genome from P. peninsularis, which will provide information for biogeographical studies and management plans for invasive species.